A corpus-based genre analysis of promotional-informational discourse in online painting exhibition overviews. (April 2023) - Işık, Elvan Eda
Abstract: Online painting exhibition overviews (OPEOs) on websites of art museums and galleries not only promote on-site exhibitions, but also inform and educate the public who might have a limited background in art. Embedding both informational and promotional discourses, the OPEO displays rhetorical hybridization, which sets it apart from predominantly univocal genres like art history texts or traditional advertisements. In line with the global increase in the number of art venues, there is a greater demand for art professionals equipped with the written English communication skills necessary to produce OPEOs. This paper aims to identify the rhetorical moves and key lexico-grammatical features in the previously underexplored genre of OPEOs through the analysis of a 35, 175- word corpus of 120 texts obtained from the websites of 20 highly reputed art museums in the UK and the US. The move analysis reveals five moves and nine steps, which can be categorized into two key discourse types: promotional and informational, according to their communicative functions. Among these, Move 2, 'justifying the exhibition', is highly significant as an obligatory move, and is most commonly recycled across the corpus. The study presents recommendations for ESP pedagogies in raising writers' awareness of the generic features of OPEOs. Highlights: Move structure of online painting exhibition overviews (OPEOs) is identified. Lexico-grammatical features of OPEOs are investigated. Justifying the exhibition, as a promotional move, is central in OPEOs. Promotional-informational discourse strategies in OPEOs are unveiled. Implications of the findings for ESP pedagogies are discussed.